Thomas James Walsh and John Edward Erickson papers - Walsh, Thomas James, 1859-1933.; Erickson, John Edward, 1863-1946.
Correspondence, speeches, legislative files, pamphlets, newspaper clippings, scrapbooks, photographs, and other papers relating chiefly to the senatorial career of Walsh and his successor, John Edward Erickson. Consists primarily of legislative files pertaining to national issues such as farm legislation, the Great Lakes and St. Lawrence Seaway route, National Council of Defense in World War I, pensions, political appointments, railway legislation, Russian famine relief, and war risk insurance. Includes material pertaining to the American Peace Society, League to Enforce Peace, Permanent Court of International Justice (World Court), and World Peace League. Issues relating chiefly to Montana include farm loan associations, Indian affairs, pardons and paroles, oil and gas permits, land cases, Flathead River power sites, and the Sun River irrigation project. Correspondents include William Edgar Borah, Albert B. Fall, Warren G. Harding, Herbert Hoover, J. Edgar Hoover, Charles Evans Hughes, Cordell Hull, Harold L. Ickes, Wesley Livsey Jones, Andrew W. Mellon, Gerald Prentice Nye, David Aiken Reed, Franklin D. Roosevelt, Elihu Root, Henrick Shipstead, Henry L. Stimson, Henry A. Wallace, and Ray L. Wilbur.
Microfilm edition of scrapbooks available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Library of Congress Music Division.
U.S. senators from Montana: Thomas James Walsh served from 1913 to 1933 and John Edward Erickson served the remainder of Walsh's last term, 1933-1934.
Collection material in English.
Keywords: Borah, William Edgar, -- 1865-1940 -- Correspondence; Fall, Albert B. -- 1861-1944 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hoover, J. Edgar -- 1895-1972 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Jones, Wesley Livsey, -- 1863-1932 -- Correspondence; Mellon, Andrew W. -- 1855-1937 -- Correspondence; Nye, Gerald Prentice, -- 1892-1971 -- Correspondence; Reed, David Aiken, -- 1880-1953 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Shipstead, Henrik, -- 1881-1960 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Wallace, Henry A. -- 1888-1965 -- Correspondence; Wilbur, Ray L. -- 1875-1949 -- Correspondence; United States. -- Council of National Defense; American Peace Society; International Court of Justice; League to Enforce Peace (U.S.); Permanent Court of International Justice; World Peace League; Agricultural credit -- Montana; Agriculture -- United States; Electric power -- Montana; Famines -- Russia; Food relief -- Russia; Indians of North America -- Montana -- Government relations; Insurance -- War risks; International law; Irrigation -- Montana; Land tenure -- Law and legislation -- Montana; Pardon -- Montana; Parole -- Montana; Peace -- Societies, etc; Pensions -- United States; Petroleum industry and trade -- Montana; Railroad law -- United States; World War, 1914-1918.; Flathead River (B.C. and Mont.); Great Lakes (North America); Montana -- Politics and government; Saint Lawrence Seaway; Sun River (Mont.); United States -- Defenses; United States -- Officials and employees -- Selection and appointment; Senators, U.S. Congress -- Montana